Prevalence of Malocclusion and Occlusal Traits in Children with Autism Spectrum Disorders - Farmani S; Ajami S; Babanouri N (Dove Medical Press, 2020)
Somaye Farmani, Shabnam Ajami, Neda Babanouri Department of Orthodontics, Orthodontic Research Center, School of Dentistry, Shiraz University of Medical Sciences, Shiraz, IranCorrespondence: Neda BabanouriDepartment of Orthodontics, Orthodontic Research Center, School of Dentistry, Shiraz University of Medical Sciences, Qom Abad Blv, Ghasrodasht AV, Shiraz, IranTel +98-713 6263193Email nedababanouri508@protonmail.comBackground: The purpose of this cross-sectional study was to evaluate the prevalence of malocclusion in children with autism spectrum disorders (ASDs) and to determine the most common occlusal traits.Materials and Methods: The present cross-sectional study was conducted among 7– 15 years old children with ASDs and randomly selected healthy children with the same demographic characteristics. Molar relationship, lip incompetence, overbite, overjet, midline deviation, crossbite, and crowding/spacing were recorded. A descriptive analysis was performed for all variables. A comparison of the presence or absence of malocclusion traits between children with and without ASDs was assessed using the chi-square test. Univariate and multivariate logistic regressions were used to calculate odds ratio (OR) and 95% confidence intervals (95% CI) to assay various parameters between autism and non-autism group.Results: A total of 96 patients were assessed, 47 patients in the ASD group, and 49 in the control (non-ASD) group. The results showed no significant difference between the ASD and control groups in terms of the overall prevalence of malocclusion (P> 0.05). However, the prevalence of increased overjet and Class II molar relationship was significantly higher in the ASD group compared to the control group (P=0.03). Patients in the control group showed a higher prevalence of midline deviation (P=0.001).Conclusion: Despite a higher prevalence of overjet and Class II molar relationship in children with ASDs, the prevalence of malocclusion was not higher in this group of patients.Keywords: prevalence of malocclusion, autism spectrum disorders, disabled child, orthodontic care